(3GdLhOI hGdGYJeGO GdGcGOjej deDSSGJ GdJYdje GdYGe hGdLGeYj (B/s - (3eLjO, ShSf TGcQs ((3YeGf(B: s (3OGQ UaGA ddfTQ(B, s, 2008)
(3JVef GdcJGH GKfG YTQ aUdG hbO JfGhd GdaUd GdGhd ef GdcJGH djeKd ebOeI JGQjNjI , heQGMd JWhQ eaghe GdLhOI hGdGYJeGO GdCcGOjej heaGgje heUWdMGJ CSGSjI aj GdLhOI hGdGYJeGO GdGcGOjej(B. (3CeG GdaUd GdKGfj abO JfGhd QhGO GdLhOI hGdfeGPL GdJj bOehgG cd MSH efWdbGJg GdacQjI hGdadSajI hGdLhGFR GdJj MOOJ ef bHdge(B. (3GeG GdaUd GdKGdK abO JfGhd GdeYGjjQ GdOhdjI ddLhOI hGdeJWdHGJ GdVQhQjI ddMUhd Ydi TgGOI GdGjRh hGdYdGbI Hjf GdLhOI hGdGjRh (B. (3hQcR GdaUd GdQGHY Ydi ehVhYGJ CgOGa heHQQGJ JWHjb GdLhOI aj eDSSGJ GdJYdje GdYGe hGdLGeYj(B. (3GeG GdaUd GdNGeS abO JfGhd eYGjjQ GdJYdje GdYGe hefgG (B( (3GOGQI GdeOQSI, hGdefgL, hGdeTGQcI GdeLJeYjI hZjQgG(B). (3CeG GdaUd GdSGOS abO JfGhd GdGSGdjH GdeSJNOeI aj JMbjb LhOI COGA GdeDSSGJ GdJQHhjI hGdLGeYjI, hefgG YedjI GdJbhje GdPGJj hGdJbhje GdNGQLj hCSdhH GdebGQfI GdeQLYjI(B. (3GeG GdaUd GdSGHY abO JVef NWhGJ JWHjb GdLhOI aj eDSSGJ GdJYdje GdYGe hGdLGeYj(B. (3GeG GdaUd GdKGef abO JfGhd GdGYJeGO GdGcGOjej deDSSGJ GdJYdje GdYGdj hGdGSGdjH GdeYJeOI aj JMbjb GdGYJeGO GdHQGeLj hGdeDSSj(B. (3hYQV GdaUd GdJGSY feGPL GdOhd GdeJbOeI aj JWHjb GdLhOI hGdGYJeGO GdGcGOjej(B. (3hYQV GdaUd GdYGTQ feGPL GdOhd GdYQHjI aj JWHjb GdLhOI hGdGYJeGO GdGcGOjej(B. (3GeG GdaUd GdMGOj YTQ abO CgJe HhVY eDTQGJ LhOI COGA GdLGeYGJ GdYQHjI heYGjjQ GdJbhje(B. (3hJfGhd GdaUd GdKGfj YTQ hGdGNjQ JUfja GdLGeYGJ hGfhGYgG hGdGSGdjH GdGMUGFjI GdeSJNOeI aj GdJUfjas
(3HjHdjhZQGajG U(B.421s
Keywords: (3GdJYdje GdYGdjs; (3GdJYdje(B-(3GdCQOfs; (3GdeDSSGJ GdJYdjejIs